2018
DOI: 10.1021/acs.jpcc.8b07513
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Activity Transition from Oxidized to Metallic Tungsten for Catalytic Hydrogenation: A Density Functional Theory Study

Abstract: Oxide-based hydrogenation catalysts have attracted intensive interest, but the relationships between their composition, structure, and reaction mechanism are still ambiguous. Here, we conducted density functional theory (DFT) calculation on ethylene hydrogenation over WO 3 , WO 2.72 , WO 2 , and W catalysts to explore how the structure and catalytic activity change with the composition and explain why neither WO 3 nor metallic W is a good hydrogenation catalyst but WO 3−x is. Calculations on the geometric and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Most notably, Mattheiss et al [18] provided the first theoretical study investigating the Fermi surface of tungsten using a nonrelativistic approach, followed by Christensen et al, who expanded on this study by calculating the band structure using a relativistic augmentedplane-wave (APW) method coupling the theory results with experimentally obtained photoelectron spectra [27,28]. More recently, theoretical investigations have transitioned from calculating tungsten's band structure to more applicationdriven investigations into the interaction of molecules with tungsten surfaces, point defect studies, or the study of nanostructures [29][30][31][32][33][34]. Several approaches have been used to calculate the projected density of states (PDOS) of tungsten, but these results have not yet been directly compared (with photoionization cross section and broadening corrections) to high-resolution valence band spectra [16,20,22,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Most notably, Mattheiss et al [18] provided the first theoretical study investigating the Fermi surface of tungsten using a nonrelativistic approach, followed by Christensen et al, who expanded on this study by calculating the band structure using a relativistic augmentedplane-wave (APW) method coupling the theory results with experimentally obtained photoelectron spectra [27,28]. More recently, theoretical investigations have transitioned from calculating tungsten's band structure to more applicationdriven investigations into the interaction of molecules with tungsten surfaces, point defect studies, or the study of nanostructures [29][30][31][32][33][34]. Several approaches have been used to calculate the projected density of states (PDOS) of tungsten, but these results have not yet been directly compared (with photoionization cross section and broadening corrections) to high-resolution valence band spectra [16,20,22,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…If there is a full coverage of hydrogen, tungsten oxide would be sequentially reduced to metal tungsten . As for the effect of coverage of H on adsorption, Jiajia Song et al found that the lower the coverage of H is, the more positive the binding before H is saturated . The main issue for hydrogen reduction would be the diffusion of hydrogen, which will be shown in our later work.…”
Section: Dft Calculationmentioning
confidence: 67%
“…[27,28] More recently, theoretical investigations have transitioned from calculating tungsten's band structure to more application-driven investigations into the interaction of molecules with tungsten surfaces, point defect studies, or the study of nanostructures. [29][30][31][32][33][34] Several approaches have been used to calculate the projected density of states (PDOS) of tungsten, but these results have not yet been directly compared (with photoionisation cross section and broadening corrections) to high-resolution valence band spectra. [16,20,22,26,27] Beyond band structure features, the photoelectron spectrum also contains satellite peaks which arise from the additional excitation of a plasmon or electron-hole pair.…”
Section: Introductionmentioning
confidence: 99%